2022
DOI: 10.3390/urbansci6010016
|View full text |Cite
|
Sign up to set email alerts
|

City-Wide Firearm Violence Spikes in Minneapolis following the Murder of George Floyd: A Comparative Time-Series Analysis of Three Cities

Abstract: This study investigates the aftermath of a high-profile violent police incident as it relates to city-wide firearm violence. Utilizing two Midwest cities (Kansas City, Missouri and Omaha, Nebraska) as comparison cities, we assess whether violent firearm incidents increased in Minneapolis after the murder of George Floyd. Multiple interrupted time-series analyses showed statistically significant increases in weekly firearm incidents in Minneapolis (AME = 10.63, p < 0.05) and Omaha (AME = 1.47, p < 0.5) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…A CRIS also evokes emotional responses that lead to polarization. This was demonstrated in [59] for the climate change topic and the topic of public opinion about police funding [64] at around the time of the murder of George 7 Human Behavior and Emerging Technologies Floyd at the hands of law enforcement in the United States [155]. It was also seen that the level of a person's stubbornness was shown to be inversely correlated to the probability of belief change [55].…”
Section: Domain-specific Dimension As Shown In Tablementioning
confidence: 89%
“…A CRIS also evokes emotional responses that lead to polarization. This was demonstrated in [59] for the climate change topic and the topic of public opinion about police funding [64] at around the time of the murder of George 7 Human Behavior and Emerging Technologies Floyd at the hands of law enforcement in the United States [155]. It was also seen that the level of a person's stubbornness was shown to be inversely correlated to the probability of belief change [55].…”
Section: Domain-specific Dimension As Shown In Tablementioning
confidence: 89%
“…One potential consequence of a lack of police turnover research (owing in part to the dearth of data we have outlined above) could be inadequately accounting for the mechanisms driving lower police activity, such as in studies linking increased violent crime to the George Floyd protest moment (Cassell, 2020). Whereas recent studies linked increased firearm violence in Minneapolis to the murder of George Floyd, that has not been the case with some comparison cities (Boehme et al, 2022). Models linking Floyd protests and crime may inadvertently mask an important causal factor: the number of officers available to deter, respond to, and investigate serious crime (Petersen et al, 2023).…”
Section: The Importance Of Studying Police Turnovermentioning
confidence: 99%
“…A growing demand for police reform accompanied these protests. While certainly not new, the Floyd moment in policing was notable for prompting the most widespread protest movement in recent memory (Boudreau et al, 2022), wide-ranging policy change, mainstream political calls for defunding and even abolishing police agencies, increased (but perhaps localized) firearm violence (Boehme et al, 2022), and rapid declines in favorable opinions of the police (Reny & Newman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… Demir and Park (2021) found that Black Lives Matter protests resulting from George Floyd's death did not lead to a change in assault CFS in Burlington, Vermont. On the other hand, there was a significant increase in reported firearm incidents after Floyd's death in Minneapolis, Minnesota, but not in two Midwestern cities used as comparison sites ( Boehme, Kaminski, & Nolan, 2022 ). Another recent study found that citizen cooperation and engagement with police (measured as the ratio of citizen CFS relative to ShotSpotter gunshot detections) significantly decreased after George Floyd's murder across eight U.S. cities ( Ang, Bencsik, Bruhn, & Derenoncourt, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%